Total and free PSA serum concentrations are not influenced by extensive physical exercise and bicycle riding - Lippi, G.; Corgnati, A.; Salvagno, G.; Schena, F.; Franchini, M.; Guidi, G. (International Journal of Sports Medicine, 2005)
Vigorous and prolonged physical exercise and mechanical involvement of the perineal region might influence prostatic function and measurement of both total (PSA) and free prostate specific antigen (fPSA), decreasing the diagnostic efficiency of the laboratory screening for either benign or neoplastic prostate disorders in athletes. To investigate the effects of regular and strenuous physical exercise with or without bicycle riding on integrity and biochemical function of prostatic tissue, we measured serum PSA and fPSA in 69 elite and professional cyclists, 31 members of the Italian national cross-country ski team, and in 43 sedentary healthy controls. The concentration of both PSA and fPSA did not differ significantly between sedentary individuals and physically active cross-country skiers (PSA 0.43 ± 0.30 vs. 0.36 ± 0.25, ns; fPSA 0.16 ± 0.12 vs. 0.12 ± 0.12, ns) or cyclists (PSA 0.43 ± 0.30 vs. 0.36 ± 0.23, ns; fPSA 0.16 ± 0.12 vs. 0.13 ± 0.08, ns), and the relative distribution of values appeared almost overlapping. We hypothesize that neither a heavy and regular physical exercise nor the extensive and prolonged mechanical involvement of the prostate region by the bicycle riding have significant influence on release of both PSA and fPSA.